Ruminal microbiome and productive response of lambs fed shrimp shell meal - Ley-de Coss, Alejandro; Morales Aguilar, Jonathan; Montañez-Valdez, Oziel Dante; Vicente Pérez, Ricardo; Guerra-Medina, Cándido Enrique (Ecosistemas y Recursos Agropecuarios, 2024)
The fishing industry produces byproducts that accumulate and cause environmental pollution problems; however, could be used as an alternative source of nutrients in ruminants. The objective of the present study was to evaluate the response over ruminal microbiome, apparent digestibility and productivity of Katahdin lambs fed different levels of shrimp shell meal (HCC). Four male lambs with live weight of 22 ± 2.5 kg were assigned in a repeated Latin square design (4 animals x 4 treatments). The animals were assigned for 16 days per period to diets with 0, 5, 10 and 20 g 100 g DM of HCC, the treatments were: HCC0, HCC5, HCC10 and HCC20, respectively. The greatest daily weight gain was found in the HCC5 treatment (P ≤ 0.05). However, the highest dry matter intake was observed in animals with the HCC20 diet (P ≤ 0.05). In the apparent digestibility of the dry matter there was no difference between treatments (P > 0.05), neither in the concentration of total bacteria (P > 0.05), while the concentration of cellulolytic bacteria and chitin-degrading bacteria was higher in the animals from HCC20 treatment (P ≤ 0.05). The results indicate an adaptation of the ruminal microbiome to high doses of HCC, therefore, HCC can be used in diets for sheep without effect on rumen metabolism and microbial, nutrient digestibility and animal performance.
Keywords: Nutrition; microbiology; sheep; chitin; byproducts